Diagnosis and Management of Hepatitis C Virus Infection. (October 2015) - Mukherjee, Ronita; Burns, Andrew; Rodden, Diane; Chang, Frances; Chaum, Manita; Garcia, Nancy; Bollipalli, Nikitha; Niemz, Angelika
The hepatitis C virus (HCV) infects more than 200 million people globally, with increasing incidence, especially in developing countries. HCV infection frequently progresses to chronic liver disease, creating a heavy economic burden on resource-poor countries and lowering patient quality of life. Effective HCV diagnosis, treatment selection, and treatment monitoring are important in stopping disease progression. Serological assays, which detect anti-HCV antibodies in the patient after seroconversion, are used for initial HCV diagnosis. Qualitative and quantitative molecular assays are used to confirm initial diagnosis, determine viral load, and genotype the dominant strain. Viral load and genotype information are used to guide appropriate treatment. Various other biomarker assays are performed to assess liver function and enable disease staging. Most of these diagnostic methods are mature and routinely used in high-resource countries with well-developed laboratory infrastructure. Few technologies, however, are available that address the needs of low-resource areas with high HCV prevalence, such as Africa and Southeast Asia.